2022
DOI: 10.4102/safp.v64i1.5609
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts among students of higher education, Nelson Mandela Bay Municipality, South Africa

Abstract: Background: Worldwide, death by suicide is a leading cause of death among young people, and students of higher educational institutions constitute a vulnerable group. This study aimed to determine the lifetime prevalence and associated factors of suicide attempt among students of a higher education institution in Nelson Mandela Municipality.Methods: A cross sectional study was conducted among students of East Cape Midland College in Nelson Mandela Municipality. The participants were selected by stratified rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Alabi (2022) reported that more than 14,000 young people aged between 15 and 29 die by suicide in South Africa every year. This mirrors the situation in densely populated countries such as Nigeria [31], where drug misuse and inadequate education about overcoming mental health challenges and the use of social media are leading young people to their early graves. As long as economic instability continues to be a challenge, the unavailability of infrastructural and social requirements and dwindling self-belief and confidence have inclined African youths to extreme solutions, including suicide [33,34].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Alabi (2022) reported that more than 14,000 young people aged between 15 and 29 die by suicide in South Africa every year. This mirrors the situation in densely populated countries such as Nigeria [31], where drug misuse and inadequate education about overcoming mental health challenges and the use of social media are leading young people to their early graves. As long as economic instability continues to be a challenge, the unavailability of infrastructural and social requirements and dwindling self-belief and confidence have inclined African youths to extreme solutions, including suicide [33,34].…”
Section: Introductionmentioning
confidence: 84%
“…Mental health, especially among young people in Africa, continues to pose a challenge. In the face of existing economic struggles and the difficulty in living up to potential, which leads to social exclusion [28,29] and interpersonal relationship struggles [30], more African young people are resorting to suicide [31]. According to the WHO (2022), 85% of Africans living in low-income countries do not have access to mental health treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In light of South Africa's culturally and socioeconomically diverse population, group cognitive-behavioral interventions with cultural components may be appropriate for South African men and women. This is crucial given that in South Africa, there are no adequate guidelines for suicide prevention within local contexts despite the existence of the national mental health policy document[ 47 ].…”
Section: Observations Based On Literature Analysesmentioning
confidence: 99%
“…providing academic support and mental health programs; however, the problem persists (Makhubela, 2021). Academic failure is the most common cause of suicide amongst students globally, including South Africa (Alabi, 2022). With these factors, suicide and poor mental health among university students is not a local phenomenon, but a global social concern which urgently needs to be eradicated (Campbell et al, 2022).…”
Section: Introductionmentioning
confidence: 99%